2020
DOI: 10.3390/rel11090475
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Distancing, and Reconciling: Religion and Race in Americans’ Abortion Attitudes

Abstract: Religion and race together inform Americans’ abortion attitudes, but precisely how remains contradictory and unclear. Presumptions of shared religious or secular “worldviews” dividing abortion opinion mask variation among racially diverse adherents within the same tradition. Theoretical gaps compel a deeper, qualitative exploration of underlying processes. This article uses close analysis of a religiously and racially diverse, ideal–typical subset of in-depth interviews from the National Abortion Attitudes Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Inclusion of the unsure response option makes our study unique compared with previous studies like the GSS, which provides participants dichotomous response options to select from. Our approach allows participants to indicate ambiguity, ambivalence, or uncertainty in opinion, which several researchers have called for in terms of abortion attitudes research (Bruce, 2020; Hans & Kimberly, 2014; Jelen & Wilcox, 2003; Jozkowski et al, 2018; Jozkowski, Crawford et al, 2021). We found that across circumstances, over 20% of people indicated being unsure as to whether abortion should be illegal given the specific circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of the unsure response option makes our study unique compared with previous studies like the GSS, which provides participants dichotomous response options to select from. Our approach allows participants to indicate ambiguity, ambivalence, or uncertainty in opinion, which several researchers have called for in terms of abortion attitudes research (Bruce, 2020; Hans & Kimberly, 2014; Jelen & Wilcox, 2003; Jozkowski et al, 2018; Jozkowski, Crawford et al, 2021). We found that across circumstances, over 20% of people indicated being unsure as to whether abortion should be illegal given the specific circumstance.…”
Section: Discussionmentioning
confidence: 99%
“… 44 As such, the labels of pro‐abortion/anti‐abortion and pro‐choice/pro‐life may yield significantly different answers. 45 Should proaborto and antiaborto be used as translations for pro‐choice and pro‐life, there appears to be a high likelihood of data incomparability between English and Spanish versions of the survey. More research is needed for each identity label, including pilot testing, conducting cognitive interviews, and validating survey drafts for data comparability.…”
Section: Discussionmentioning
confidence: 99%
“…As debates about the Hyde Amendment are likely to intensify in the coming years, this analysis is intended to lay the groundwork for more research and to encourage the collection of more data on Americans' attitudes toward public funding of abortion. Future research should especially focus on changes in these attitudes over time; on the effects of question wording on these attitudes; on how these attitudes are shaped by other factors like gender, race, or education; and following Bruce (2020aBruce ( , 2020b, on qualitative investigations of how people think about this complex issue.…”
Section: Discussionmentioning
confidence: 99%